1994
DOI: 10.1073/pnas.91.9.3544
|View full text |Cite
|
Sign up to set email alerts
|

Cation-promoted association of a regulatory and target protein is controlled by protein phosphorylation.

Abstract: In enteric bacteria, the phosphoenolpyruvate:glycose phosphotransferase system (PTS) catalyzes the uptake and phosphorylation of its sugar substrates. In addition, the PTS regulates adenylate cyclase, glycerol kinase (GK), and a number of non-PTS permeases (for reviews, see refs. 1-4). In the present report, we show that the binding of IIIic to GK generates a putative intermolecular zinc coordination site. Zn(II) not only specifically binds at this site but substantially increases the apparent affinity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
6
40
0
Order By: Relevance
“…The parameters obtained from the fit show that binding of III Glc gives 95% inhibition of the wild-type enzyme but gives twofold, i.e., 100%, activation of the G-304-S enzyme. For the wild-type enzyme, the apparent dissociation constants for III Glc binding are 15 M in the absence of Zn(II) and 0.6 M with 0.1 mM Zn(II), values which agree with our previous report (5). For the G-304-S enzyme, the corresponding values are 110 and 9 M. Thus, the G-304-S substitution decreases the apparent affinity for III In the related protein DnaK, conformational change due to ATP binding affects cleavage by proteases (9).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The parameters obtained from the fit show that binding of III Glc gives 95% inhibition of the wild-type enzyme but gives twofold, i.e., 100%, activation of the G-304-S enzyme. For the wild-type enzyme, the apparent dissociation constants for III Glc binding are 15 M in the absence of Zn(II) and 0.6 M with 0.1 mM Zn(II), values which agree with our previous report (5). For the G-304-S enzyme, the corresponding values are 110 and 9 M. Thus, the G-304-S substitution decreases the apparent affinity for III In the related protein DnaK, conformational change due to ATP binding affects cleavage by proteases (9).…”
Section: Resultssupporting
confidence: 82%
“…We are investigating the molecular basis of these allosteric control mechanisms by which glycerol kinase functions in a signal transduction pathway that modulates gene expression in response to carbon source availability. The crystal structure of the complex of glycerol kinase with the unphosphorylated form of III Glc has been determined (8), and the association of the two proteins forms a novel intermolecular binding site for Zn(II) (5). A proposed mechanism for FBP regulation postulates that FBP binds to and inhibits the tetrameric form of the enzyme (3).…”
mentioning
confidence: 99%
“…Indeed, crystals soaked in a 20 mM ZnCl 2 solution adopted a Zn 2ϩ ion at the expected position (223). Subsequent in vitro studies revealed that the presence of the metal ion lowers the K i of EIIA Glc for GlpK by about 60-fold (223,616 It is not known how the interaction with unphosphorylated EIIA Glc inhibits glycerol phosphorylation. The more than 30-Å distance between the sites of EIIA Glc binding and glycerol phosphorylation rules out a direct effect.…”
Section: Inhibits Transcription Induction Mechanismmentioning
confidence: 99%
“…The question arises how the PTS can still regulate other systems by inducer exclusion under these conditions, because unphosphorylated IIA Glc binds stoichiometrically to its target proteins. Additional simulations (54) have shown that introduction of a step for binding of free unphosphorylated IIA Glc to a target protein leads to a redistribution of the IIA Glc forms and that a significant fraction of the total IIA Glc can bind to the target protein if the dissociation equilibrium constant is in the range of 0.2-1 M, as reported for glycerol kinase and IIA Glc in the presence of Zn(II) (55). However, the addition of glucose by itself to a suspension of E. coli cells (i.e.…”
Section: Iiamentioning
confidence: 99%